2018
DOI: 10.3389/fonc.2017.00327
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anaplastic Embryonal Rhabdomyosarcoma: Targeted Therapy Guided by Genetic Analysis and a Patient-Derived Xenograft Study

Abstract: Therapy for rhabdomyosarcoma (RMS) has generally been limited to combinations of conventional cytotoxic agents similar to regimens originally developed in the late 1960s. Recently, identification of molecular alterations through next-generation sequencing of individual tumor specimens has facilitated the use of more targeted therapeutic approaches for various malignancies. Such targeted therapies have revolutionized treatment for some cancer types. However, malignancies common in children, thus far, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…With the recent identification of mutations in epigenetic remodelers in WT, and their interaction with histone deacetylases (HDAC), inhibitors of the latter might be another promising avenue. Transient response to single agent vorinostat, an HDAC inhibitor, was demonstrated in a child with refractory anaplastic embryonal rhabdomyosarcoma harboring mutations in BCOR and ARID1A (142). A further potential target is TP53, given the prevalence of TP53 mutants in both anaplastic and non anaplastic fatal tumours (41).…”
Section: How Can This New Knowledge Of Somatic Cancer Genes In Wilms Lead To Novel Treatments?mentioning
confidence: 99%
“…With the recent identification of mutations in epigenetic remodelers in WT, and their interaction with histone deacetylases (HDAC), inhibitors of the latter might be another promising avenue. Transient response to single agent vorinostat, an HDAC inhibitor, was demonstrated in a child with refractory anaplastic embryonal rhabdomyosarcoma harboring mutations in BCOR and ARID1A (142). A further potential target is TP53, given the prevalence of TP53 mutants in both anaplastic and non anaplastic fatal tumours (41).…”
Section: How Can This New Knowledge Of Somatic Cancer Genes In Wilms Lead To Novel Treatments?mentioning
confidence: 99%
“…The embryonal RMS subtype typically affects younger children and is generally comprised of PAX-negative tumors. A rare subtype of RMS is anaplastic, where a single case was recently reported to carry a BCOR alteration, together with mutation in ARID1A , a member of the SWI/SNF family, and of SETD2 , a histone methyl-transferase [61]. Two studies [131,132] confirmed that BCOR mutations in RMS recur in about 7–8% of total cases, with an apparent major involvement in PAX-negative RMS, for which the percentage nears 10% of cases (Table 2).…”
Section: Sarcomasmentioning
confidence: 99%
“…5 In the paediatric population, the two main histological subtypes of RMS are embryonal and alveolar, with embryonal RMS accounting for nearly 70% of all cases and usually affecting children less than 8 years of age. 1,6 Histopathologically, RMS is characterised by myoblastic differentiation and expression of skeletal muscle markers, such as desmin, myogenin and/or myoD1. 6…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Histopathologically, RMS is characterised by myoblastic differentiation and expression of skeletal muscle markers, such as desmin, myogenin and/or myoD1. 6…”
Section: Discussionmentioning
confidence: 99%